Second Language between marginalization and social inclusion. Qualitative survey on SL training services and on the social inclusion needs of migrants, an intercultural and postcolonial reading - Aurora Bulgarelli (University of Bologna, 2023)
In the migrant's path to social inclusion, learning the Second Language (SL) is a fundamental step and the educational environments can represent heterogeneous ideological spaces for the emergence of multivocal narratives (Chakrabarty, 2004). SL education can reproduce colonial relations, determining forms of subordinate integration based on the social structural asymmetries and that finds one of the regulatory principles in the category of race (Fanon, 1961). At the same time, SL education can promote an intercultural and problem posing education (Freire, 2018), committed to deconstructing these relationships with Otherness. This contribution deals with some aspects of broader doctoral research, relating to the topic of SL and the inclusiveness, or marginalisation, of educational action. The qualitative investigation was carried out in the city of Rome through 60 semi-structured interviews. What emerged is that the different perception of the SL influences the migrant's path to social inclusion as learning can respond to social and emancipatory needs, but also to needs linked to the socio-economic dimension and the fulfillment of regulatory requirements, leading to a risk of social exclusion.